Nem teúdas, nem manteúdas História das Mulheres e Direito na capitania da Paraíba (Brasil, 1661-1822) - de Oliveira Coutinho Silva, Luisa Stella (Global Perspectives on Legal History, 2020)
This book develops a legal history of colonial women as a methodological approach to studying the women of Paraíba, a captaincy on the northeast coast of Brazil, from the end of the Dutch occupation (1661) to Brazilian independence in 1822. It uses the concept of multiple normativities to analyse dozens of daily life cases from Portuguese and Brazilian archives. To study women's everyday normative contexts in a colonial space, the author analyses traditional Ius Commune and Portuguese legal sources from different jurisdictions, but also legal doctrines, medical treatises, moralist works and literature to enrich interpretations in women's history, gender studies, feminist legal theory and legal history. Furthermore, she examines the impact of these normative traditions in the colonial Captaincy of Paraíba and focuses on normativities of a more pragmatic character, analysing archival documents portraying women's daily life situations relating to both secular and religious jurisdictions. The analysis demonstrates that the law from the metropole neither offered pre-established solutions for women's daily lives, nor was it applied unchanged in the colony. On the ground, law was dynamic, and the interplay of multiple normativities provided different possibilities that depended on the intersection of women's condition and status, religion and sexual options, proving that sex and gender categories are not immutable, but, on the contrary, flexible according to the practices of law in colonial Paraíba.